Performance of UC Davis chimney dryer: time saving and retention of nutritional quality of carrot and brinjal - Pias, Shamsudduha; Islam, M Tariqul; Rahim, M Abdur; Sheikh, Alamin; Islam, M Ashraful (Fundamental and Applied Agriculture, 2020)
UC Davis (University of California, Davis) chimney dryer is a low cost technology and has been developed by the expert of UC Davis, USA to dry food products targeting to ensure the nutritional security. Experiments were conducted following completely randomized design with three replications. Slice thickness of carrot (experiment 1) was 1.5 cm with and without skin while thickness of brinjal (experiment 2) was 1 and 2 cm. Overall, less time required to dry both carrot and brinjal under UC Davis chimney dryer compared to sun dryer condition. Carrot drying time was 82 hours under UC Davis chimney dryer whereas 122 hours required to dry under open sun drying condition; so UC Davis saved 34% time to dry carrot compared to open sun dry condition. Similarly, 21 to 25% time has been saved for brinjal drying under UC Davis chimney dryer compared to open sun dryer condition. No significant difference of protein, phosphorus and potassium contents of carrot and brinjal found from both systems of dryer indicating the no deterioration of mineral contents due to high temperature in UC Davis chimney dryer. Moisture and dry matter contents were also significantly different from each other. Overall, acceptance of physical appearance of both carrot (without skin) and brinjal (1 cm sliced thickness) was selected as the best under UC Davis chimney dried product compared open sun dried product, considering shape, size and colour of the dried products. UC Davis chimney dryer can efficiently reduce the duration of drying of vegetables and also avoid noise from birds and dusts compared to open sun dryer condition; and products can be stored for long time, thus ultimately provide nutritional security round the year for the rural people.